Prediction of the Scale Removal Rate in Heat Exchanger Piping System Using the Analogies between Mass and Momentum Transfer - Majeed, Najwa S. (Al-Khwarizmi Engineering Journal, 2010)
The possibility of predicting the mass transfer controlled CaCO3 scale removal   rate has been investigated.Experiments were carried out using chelating agents as a cleaning solution at different time and Reynolds’s number. The results of CaCO3 scale removal or (mass transfer rate) (as it is the controlling process) are compared with proposed model of prandtl’s and Taylor particularly based on the concept of analogy among momentum and mass transfer.Correlation for the variation of Sherwood number ( or mass transfer rate ) with Reynolds’s number have been obtained .